STUDI KANDUNGAN KATEKIN DAN TURUNANNYA SERAGAI ANTIOKSIDAN ALAMI SERTA KARAKTERISTIK ORGANOLEPTIK PRODUK TEH MURREI DAN TEH CAMELLIA-MURREI - Evy Damayanthi; Clara Meliyanti Kusharto; Rohayati Suprihatini; Dadan Rohdiana (Media Gizi dan Keluarga, 2008)
ABSTRACT. It was reported that the Camellia tea contained of poliphenol 25-35 percent and other compounds which is goodfor health. Whereas bioactive compound i.e. Catechin and its derivatives ofgreen tea have been reported to have a beneficial effects on human health for example as anti cancer to prevent stroke and heart disease. The objectives ofthis research were to study the effect ofvariety and processing ofcamelliamulberry tea on bioactive compounds i. e. catechin and its derivatives; and to conduct organoleptic test. The Clone Gambung 7 and 9 of Camellia sinensis var. assamica; Kanva and Morus multicaulis of varieties of mulberry were used as main ingredients. Mulberry leaves were processed by enzymatic oxidative and non enzymatic oxydative, while Camellia leaves processed with non- enzymatic oxidative reaction. Thereafter, Camellia and mulberry was mixed in to ratio I: 1 (w/w, db). The chemical analysis for the content of theaflavin, tannin, cafein, catechin and its derivatives and organoleptic test were successfully conducted. The study showed the theaflavin, tannin and cafein content for fresh mulberry are 0,0690 and 0,0555 percent (db); 0,229 and 0,451 percent(db); 0,683 and 0.465 percent (db), correspo'ldingly. Theaflavin and tannin compounds of mulberry tea were found least content than Camellia-mulberry tea. There are three good formulas of Camellia-mulberry tea: start with a high rank M multicaulis-nonoxidizedGambung 7; Kanva-nonoxidized-Gambung 9 and M multicaulis-nonoxidized-Gambung 7, where mean value oftheaflavin mid tannin are 2.7968 percent db; 2.7/73 percent db; and 2.6575 percent db, correspondingly. A highest value of catechin was found in M multicaulis-oxidized-Gambung 7 (2.85%). The highest value of total catechin Kanvanonoxidized- Gambung 9 (3.91%), andfollowed by M multicaulis-nonoxidized-Gambung 7 (2.57%); and was M multicaulis-oxidized-Gambung 7 (2.33%). Organoleptic test of these formulas have moderate value, fairly sweet and strenght.Keywords Catechin, poliphenol. Camellia sinensis var. assamica, mulberry, tea. oxidative reaction